2018
DOI: 10.1080/01612840.2017.1395500
|View full text |Cite
|
Sign up to set email alerts
|

Education Needs of Families of Transgender Young People: A Narrative Review of International Literature

Abstract: Education plays a crucial role in the lives of families of transgender young people and mental healthcare practitioners are well-placed to support families in this regard. This paper reports findings from a narrative review of 31 papers that explored the education needs of families of transgender young people. The emergent themes were synthesised to develop a five-stage model that depicts the role of education in the lives of these families. Key themes included: (i) learning that a family member is trans; (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…This high proportion of mother may be explained by research which has found that mothers may often take a primary role in supporting gender identity issues within the family, with fathers possibly experiencing greater challenges in accepting a trans child (Hill & Menvielle, 2009;Kuvalanka et al, 2014;Riggs & Due, 2015;Wren, 2002). This disproportionate representation of mothers has also been found in other international studies related to education for families of trans young people (Sharek et al, 2018). Within the interviews, parents emphasised the need for siblings of trans young people to have greater access to information and support.…”
Section: The Need For Family-wide Education and Informationmentioning
confidence: 79%
See 1 more Smart Citation
“…This high proportion of mother may be explained by research which has found that mothers may often take a primary role in supporting gender identity issues within the family, with fathers possibly experiencing greater challenges in accepting a trans child (Hill & Menvielle, 2009;Kuvalanka et al, 2014;Riggs & Due, 2015;Wren, 2002). This disproportionate representation of mothers has also been found in other international studies related to education for families of trans young people (Sharek et al, 2018). Within the interviews, parents emphasised the need for siblings of trans young people to have greater access to information and support.…”
Section: The Need For Family-wide Education and Informationmentioning
confidence: 79%
“…The evidence which has emerged from other areas, including mental health (Barak, Hen, Boniel-Nissim, & Shapira, 2008;Taylor-Rodgers & Batterham, 2014;Ybarra & Eaton, 2005), family support following traumatic brain injury (Wade, Carey, & Wolfe, 2006), and parent training (Breitenstein, Gross, & Christophersen, 2014;Enebrink, Hogstrom, Forster, & Ghaderi, 2012) supports the efficacy of online learning, substantiating a need for its further investigation within the area of education for families of trans young people. However, there remains a distant lack of relevant online programs to support families of trans young people (Sharek, Huntley-Moore, & McCann, 2018). To address this gap in resources, an online education program, GenderEd.ie, was developed as part of a larger study.…”
mentioning
confidence: 99%
“…For those seeking psychological therapy, it was sometimes necessary to pay for psychological therapies, with significant financial cost implications for some. Further, children and families of trans people continue to lack the necessary psychosocial interventions and supports, further highlighting the need for education and practice development in this area (Sharek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Research has increased on the health of transgender individuals (e.g., Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013;Downing & Przedworski, 2018) and the education needs of their families (Sharek, Huntley-Moore, & McCann, 2018). Citing an Institute of Medicine Report (IOM) from 2011, Buchholz had noted that the research base on transgender-specific issues was once "so thin that the word 'gap' wasn't applicable" (cited in Buchholz, 2015, p. E1).…”
mentioning
confidence: 99%
“…In many of the newer articles, authors are moving beyond recitation of the statistics about mental disorders of transgender people, and the inept and unkind care they often receive, to describing resilience of transgender people (Bockting et al, 2013) and ways to create an atmosphere of transinclusivity in all settings of medical and psychiatric care (Abeln & Love, 2019). Issues in Mental Health Nursing has contributed toward closing the gaps in the literature, as evidenced by the excellent articles we have recently published by McCann and Brown (2018), Harmon and Donohue (2018), Sharek, et al (2018), Flaskerud and Lesser (2018), and Abeln and Love (2019). Progress is being made, and will continue with your manuscript submissions.…”
mentioning
confidence: 99%